2009
DOI: 10.1111/j.1537-2995.2009.02196.x
|View full text |Cite
|
Sign up to set email alerts
|

Stored red blood cell supernatant facilitates thrombin generation

Abstract: Some stored RBCs release RCMVs, which express PS and are capable of facilitating thrombin generation in vitro. This provides a possible mechanism by which stored RBCs could promote adverse thrombotic or inflammatory effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(52 citation statements)
references
References 61 publications
3
48
1
Order By: Relevance
“…The procoagulant properties of erythrocyte-and plateletderived microvesicles are well described in the literature and are mainly based on solid-phase in vitro assays of thrombin generation. 18,38 As in our model, the specific thrombin-inhibitor refludan was able to prevent both RBC-MV-induced complement activation in vitro (assessed by binding of C3 fragments to RBC-MV) and in vivo (evidenced by reduced C5a levels in the presence of refludan), our findings support the concept of thrombin-induced complement activation.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The procoagulant properties of erythrocyte-and plateletderived microvesicles are well described in the literature and are mainly based on solid-phase in vitro assays of thrombin generation. 18,38 As in our model, the specific thrombin-inhibitor refludan was able to prevent both RBC-MV-induced complement activation in vitro (assessed by binding of C3 fragments to RBC-MV) and in vivo (evidenced by reduced C5a levels in the presence of refludan), our findings support the concept of thrombin-induced complement activation.…”
Section: Discussionsupporting
confidence: 76%
“…18 Moreover, thrombin can function both as a C5 and C3 convertase [31][32][33] and therefore can activate complement independent of the classical or alternative pathway. Consistent with these studies, C3 fragment binding after incubation of RBC-MV with plasma in vitro could be prevented completely when plasma was used from mice anticoagulated with either heparin (not shown) or refludan, a specific thrombin inhibitor ( Figure 5A).…”
Section: Inhibition Of Thrombin Prevents Complement Activation In Vitmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published study showed that RBCs stored for longer periods of time have thrombotic or inflammatory effects. 32 RBC components are stored with a variety of solutions, which can potentially affect the aging process of the RBCs. 33 Among the most common solutions are CPD (trisodium citrate, dextrose, and disodium phosphate) and acidic additive solutions.…”
Section: Rbc Transfusions and Nhl 2905mentioning
confidence: 99%
“…A number of mechanisms have been postulated to explain this finding [45]. The microparticles shed from the RBC membrane contain high concentrations of phosphatidyl-l-serine, a potent promoter of factor VIIa activation and thrombin generation [46]. Plasminogen activator inhibitor 1 (PAI-1) accumulates in stored blood.…”
Section: Transfusion-associated Thrombosismentioning
confidence: 99%